Worshipping Athena: Panathenaia and Parthenon - Neils, Jenifer (Wisconsin studies in classics, 1996)
Theseus and Athenian festivals / Erika Simon -- Athena's shrines and festivals / Noel Robertson -- Women in the Panathenaic and other festivals / Mary R. Lefkowitz -- Group and single competitions at the Panathenaia / Alan L. Boegehold -- Gifts and glory : Panathenaic and other Greek athletic prizes / Donald G. Kyle -- Panathenaic amphoras : the other side / Richard Hamilton -- Shield devices and column-mounted statues on Panathenaic amphoras : some remarks on iconography / Michalis Tiverios -- Pride, pomp, and circumstance : the iconography of procession / Jenifer Neils -- The web of history : a conservative reading of the Parthenon frieze / Evelyn B. Harrison -- Democracy and imperialism : the Panathenaia in the age of Perikles / H.A. Shapiro